(untitled) (Journal of Philosophy Culture and Political Science, 2019)
It is considered in the article the role of Kazakh spiritual leaders in the forming of spiritual values in folk’s consciousness. Also it is opened the contribution of such social and religious activists as K. Konyratbaiuly, Baimen Ahun Tlemisuly, Kalzhan Ahun etc. Keywords: kazakh religious ﬁ gures, islam values, religious education, state religion, the consciousness of the people.